Use of sildenafil citrate in cases of intrauterine growth restriction (IUGR); a prospective trial - Mohammed Maged; Alaa Wageh; Maher Shams; Abdlgawad Elmetwally (Elsevier, 2018)
Objective: Intrauterine growth restriction (IUGR) is one of the most serious complications of pregnancy. Up to date, there is no evidence of achieving antenatal treatment of IUGR with abnormal placentation. Although, Sildenafil citrate has shown promising results, there are no firm conclusion till now. The aim of our study is to evaluate the use of Sildenafil citrate in the treatment of IUGR cases associated with impaired placental circulation. Materials and methods: This was a prospective non-randomized study conducted at Mansoura university hospitals starting from March 2016 till October 2017. The studied population included singleton pregnancy and suffering from IUGR associated with impaired placental circulation. Results: This study included 50 pregnant women. Cases were divided into two groups. The first group received sildenafil citrate and the second control group did not receive sildenafil citrate. After 4 weeks after the 1st dose of Sildenafil significant decrease in umbilical artery Doppler indices. There was a statistically significant difference in the mean birth weight at delivery and neonatal admission to the newborn nursery in sildenafil group. Conclusion: sildenafil citrate treatment may present a new hope towards better perinatal outcomes for pregnancies complicated by IUGR and impaired placental circulation that may help to decrease neonatal admission to the newborn nursery. Keywords: IUGR, Sildenafil citrate, Impaired placental circulation, Doppler ultrasonography